Paleoenvironmental reconstructions and greenhouse gas characterization in permafrost aquatic systems of Central Yakutia (Siberia) - Hughes-Allen, Lara (CCSD, 2022)
In Central Yakutia (Eastern Siberia, Russia), persistent freezing temperatures, flat topography, and a lack of glaciation during the Last Glacial Maximum (~20,000 years ago) have created optimal conditions for the proliferation of deep, ice-rich permafrost. Past and present climate change and other disturbances can have significant effects on permafrost landscapes and the global carbon budget. In areas of ice rich permafrost, degradation can result in the formation of thermokarst (thaw) lakes, which are hotspots for biological activity and greenhouse gas (GHG) emissions. The three axes of this thesis combine provide insights into 1) past lake dynamics, 2) spatial and temporal heterogeneity in GHG concentrations and diffusive fluxes from thermokarst lakes, and 3) large scale analysis of recent (since 1960s) lake dynamics in response to local climate trends and human activities.To understand lake development, sediment and organic carbon accumulation, and changes in primary productivity, within the context of Late Pleistocene and Holocene climate change, a multi-proxy paleolimnological analysis of a sediment core sequence from Lake Malaya Chabyda in Central Yakutia (Eastern Siberia, Russia) was conducted. Age-depth modeling with ¹⁴C indicates that the maximum age of the sediment core is ~14 cal kBP. Three distinct sedimentary units were identified within the sediment core. Sedimentological and biogeochemical properties in the deepest section of the core suggests a lake environment mostly influenced by terrestrial vegetation, where organic carbon accumulation might have been relatively low (average ~ 100 g OC m-2 a-1), although much higher than the global modern average. The middle section of the core was characterized by higher primary productivity in the lake, much higher sedimentation, and a strong increase in organic carbon (OC) delivery (average ~300 g OC m-2 a-1). Conditions in the upper section of the core (< 376 cm; < 9.0 cal kBP) suggest high primary productivity in the lake and high OC accumulation ...